Clinical Operations Variables are Associated With Blood Pressure Outcomes. Issue 6 (June 2015) - Kressin, Nancy R.; Lasser, Karen E.; Paasche-Orlow, Michael; Allison, Jeroan; Ash, Arlene S.; Adams, William G.; Shanahan, Christopher W.; Legler, Aaron; Pizer, Steven D.
Abstract : Background: Uncontrolled blood pressure (BP), among patients diagnosed and treated for the condition, remains an important clinical challenge; aspects of clinical operations could potentially be adjusted if they were associated with better outcomes. Objectives: To assess clinical operations factors' effects on normalization of uncontrolled BP. Research Design: Observational cohort study. Subjects: Patients diagnosed with hypertension from a large urban clinical practice (2005–2009). Measures: We obtained clinical data on BP, organized by person-month, and administrative data on primary care provider (PCP) staffing. We assessed the resolution of an episode of uncontrolled BP as a function of time-varying covariates including practice-level appointment volume, individual clinicians' appointment volume, overall practice-level PCP staffing, and number of unique PCPs. Results: Among the 7409 unique patients representing 50, 403 person-months, normalization was less likely for the patients in whom the episode starts during months when the number of unique PCPs were high [the top quintile of unique PCPs was associated with a 9 percentage point lower probability of normalization ( P <0.01) than the lowest quintile]. Practice appointment volume negatively affected the likelihood of normalization [episodes starting in months with the most appointments were associated with a 6 percentage point reduction in the probability of normalization ( P =0.01)]. Neither clinician appointment volume nor practice clinician staffing levels were significantly associated with the probability of normalization. Conclusions: Findings suggest that clinical operations factors can affect clinical outcomes like BP normalization, and point to the importance of considering outcome effects when organizing clinical care.